2018
DOI: 10.1016/j.jevs.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Ovum Pick Up and In Vitro Maturation of Jennies Oocytes Toward the Setting Up of Efficient In Vitro Fertilization and In Vitro Embryos Culture Procedures in Donkey ( Equus asinus )

Abstract: Most wild and domestic donkey breeds are currently endangered or threatened. Their preservation includes the creation of a Genome Resource Bank. Embryo cryopreservation allows preservation of genetics from both male and female and is the fastest method to restore a breed. Embryo production in vivo is limited in equids. We recently established a technique of ovum pick up (OPU) in the donkey. Conditions of in vitro maturation (IVM), in vitro fertilization (IVF), and in vitro culture of zygotes have been evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The time interval between animal death and harvesting of PFF samples could lead to postmortem accumulation of lactate (Tews et al, 1963), as reported by a previous study carried out with equine oviductal fluid (González-Fernández et al, 2020). TCM-199 is the basic culture medium most used for the formulation of IVM media in horses and in the attempts carried out so far in donkeys (Goudet et al, 2015;Deleuze et al, 2018;Zhao et al, 2011;Abdoon et al, 2014;Douet et al, 2019). When comparing our results to the metabolites described in TCM-199 culture medium (see Table 2), we detected that only 11 of the 27 metabolites found in jenny PFF were present in TCM-199 medium.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The time interval between animal death and harvesting of PFF samples could lead to postmortem accumulation of lactate (Tews et al, 1963), as reported by a previous study carried out with equine oviductal fluid (González-Fernández et al, 2020). TCM-199 is the basic culture medium most used for the formulation of IVM media in horses and in the attempts carried out so far in donkeys (Goudet et al, 2015;Deleuze et al, 2018;Zhao et al, 2011;Abdoon et al, 2014;Douet et al, 2019). When comparing our results to the metabolites described in TCM-199 culture medium (see Table 2), we detected that only 11 of the 27 metabolites found in jenny PFF were present in TCM-199 medium.…”
Section: Discussionmentioning
confidence: 90%
“…In equids, the production of in vivo-derived embryos from donors is limited by the lack of efficiency in superovulation treatments (Squires et al, 2003;Smits et al, 2012;Meyers-Brown et al, 2011), thus reducing the number of embryos available to one per oestrus cycle (Smits et al, 2012;Goudet et al, 2015;Deleuze et al, 2018). In addition, the large size of recovered in vivo embryos makes them "bad candidates" for cryopreservation (Choi and Hinrichs, 2017;Herrera et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superior sperm recovery obtained herein using retrograde flushing and then slicing float-up methods can have an even more impactful effect in the equid breeding industry than previously; nowadays, with the widespread use of intracytoplasmic sperm injection (ICSI) in horses [ 18 ] and more recently in donkeys [ 19 ], it has allowed maximum use of frozen sperm as 1000–10,000-fold less sperm is needed to result in a pregnancy in comparison with artificial insemination. As a result, many veterinary practices and clinicians are now simultaneously freezing sperm for use via artificial insemination and ICSI.…”
Section: Discussionmentioning
confidence: 99%